A novel inhibitor of farnesyltransferase with a zinc site recognition moiety and a farnesyl group. Issue 16 (15th August 2017) - Tanaka, Ayumi; Radwan, Mohamed O.; Hamasaki, Akiyuki; Ejima, Asumi; Obata, Emiko; Koga, Ryoko; Tateishi, Hiroshi; Okamoto, Yoshinari; Fujita, Mikako; Nakao, Mitsuyoshi; Umezawa, Kazuo; Tamanoi, Fuyuhiko; et al.
Graphical abstract: Abstract: Protein prenylation such as farnesylation and geranylgeranylation is associated with various diseases. Thus, many inhibitors of prenyltransferase have been developed. We report novel inhibitors of farnesyltransferase with a zinc-site recognition moiety and a farnesyl/dodecyl group. Molecular docking analysis showed that both parts of the inhibitor fit well into the catalytic domain of farnesyltransferase. The synthesized inhibitors showed activity against farnesyltransferase in vitro and inhibited proliferation of the pancreatic cell line AsPC-1. Among the compounds with farnesyl and dodecyl groups, the inhibitor with a farnesyl group was found to have stronger and more selective activity.